BENTUK PEMANFAATAN LAHAN PEKARANGAN DI DAERAH MAEK KECAMATAN BUKIK BARISAN KABUPATEN LIMA PULUH KOTA - Enwati, Rice Refni; Erita, Yeni; U, Iswandi (STKIP PGRI Sumbar, 2013)
Communities in the Maek village Bukik Barisan district existing among people who use their home gardens, although there is still a part of the community that the yard was left abandoned and overgrown with weeds that there is no benefit. Enough land that could potentially be exploited for subsistence and to supplement family income. The objective was to obtain and analyze the data or Â in-depth information about the courtyard in the form of Regional Land Use in Maek village Bukik Barisan district Lima Puluh Kota region.This research is qualitative . Location of the study villages Maek . Number of informants study of 15 people, which is taken purposive.Teknik data collection are interviews, observations, data validity checking is dokumentasi. Technique of observation Extension, perseverance observation, triangulation and peer examination through discussion. Techniques of data analysis are 1) data reduction, 2) Data Display, 3) Data Interpretation and 4) Conclusion.The results showed : 1) people take advantage of the beauty of the yard for flowers, but not all people can use the yard for beauty due to of animals, (2) The public use the land for agricultural yard to eat everyday such as vegetables and fruits. Utilization is in accordance with the principle of utilizing every inch of land for beneficial plants, (3) The public use the land for a small farm yard like chickens, ducks and forth. Yard that used generally in the rear of the house